Inhibitory Effect of Neem Leaves on Glucose Transport - Lia Safitrie Johansyah; Vycke Yunivita; Anna Martiana; Augusta Y. L. Arifin (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Neem leaf is known as a diabetic herbal treatment in India, however, its antihyperglycemic effect and the mechanism is still unknown. Quercetin is proven to inhibit glucose transporter in the small intestine, and this active substance is present in Neem leaves. The study was conducted to explore the inhibitory effect of Neem leaves infusion on glucose transport and whether the effect was reversible or irreversible.Methods: This study was conducted in the Biochemistry Laboratory Faculty of Medicine Universitas Padjadjaran in the period of October to November 2012 by using in situ perfusion method. Five male Wistar rats were given three treatments; glucose as initial control, glucose with Neem infusion, and glucose again as last control. The samples of perfusion solution were taken for every treatment and were measured using spectrophotometry method.Results: There was a reduction in glucose absorption (15.9%) between the first (47.28+17.57 mg/dL) and the second treatment (39.75+14.85 mg/dL). The transported glucose level in the third treatment was further reduced after the first treatment (37.15+13.15 mg/dL).Conclusions: Neem leaves infusion has inhibitory effect on glucose transport that irreversibly reduced further. Further study is needed with a larger sample size to confirm this phenomenon.